The Implementation of a Learning Management System for Improving Teacher Knowledge and Skills in MTs. Teladan Medan - Fadhillah Azmi; Amir Saleh; N P Dharshinni; Despaleri Perangin-Angin (Jurnal Pengabdian UNDIKMA, 2023)
The implementation of community service (PKM) aims to improve teachers' ability to teach by applying the website-based learning management system (LMS) application at MTs. Teladan Medan is the location of the dedication that has been done. The application that had been developed was a contribution to PKM partners to helped the school conduct learned management, especially in implementing online learned.Â  PKM activities were carried out through several activities, namely: socialization, training, and assistance in the used of the website-based learned management system (LMS) application that had been developed for several 16 teachers. The instruments used in the form of questionnaires, pretests, and posttests were distributed before and after the training. Based on the results of the activities carried out, there was an increase in teacher knowledge about integrated learning technology using the learning management system application, with a score of 75.65%, and an increase in teacher skills in using or applying the learning management system application, with a score of 80.47%.